Produção e recuperação de xilose redutase a partir do hidrolisado do bagaço do pedúnculo do caju (Anacardium occidentale L.) - Lemos, Leanderson Túlio Marques (2017)
The large volume of waste disposal generated by agroindustries causes serious damage to the environment. The emerging alternative is the use of these discarded materials as a source of energy for the generation of bioproducts. Within this problem, a potential reuse route for the use of cashew fruit pulp is the production of high value substances through biotechnology. The extraction of enzymes from the metabolism of yeasts, which transform the biomass into products such as xylitol and ethanol is a technique to be optimized. The objective of this research was to produce and recover the xylose reductase enzyme from the hydrolysed liquor of the cashew peduncle, with yeast Candida guilliermondii CCT 1516 as a fermentation agent. The characterization of the lignocellulosic composition of the dried cashew peduncle bagasse revealed the presence Of 29.26 ± 0.40% of cellulose, 17.06 ± 0.42% hemicellulose and 30.13 ± 0.90% lignin. The dry cashew peduncle bagasse was subjected to acid hydrolysis to liberate the plant matrix pentoses and hexoses. The hydrolyzate contained a xylose content of 6.25 g.L-1, being the highest concentration among the sugars present. The yeast Candida guilliermondii CCT 1516 presented a maximum growth rate of 0.08 g.L-1.h-1, in the medium with hydrolyzed liquor. The productivity of xylitol had a maximum value of 0.43 g.L-1.h-1 at the 36 hour culture time. And the conversion of xylose to xylitol presented a factor of 0.62 g.g-1 with efficiency of 67.61%. The activity of xylanases was affected in the first 20 h of fermentation, being a period of adaptation to the medium, later growing to reach the maximum value of 0,408 U / mL, in the time of 28 hours.